Screening and Verification of Molecular Markers and Genes Related to Salt-Alkali Tolerance in Portunus trituberculatus - Zhang, Wen; Zhao, Xiao Yan; Wu, Jie; Jin, Ling; Lv, Jianjian; Gao, Baoquan; Liu, Ping (Frontiers in Genetics, 2022)
Salt-alkali tolerance is one of the important breeding traits of Portunus trituberculatus. Identification of molecular markers linked to salt-alkali tolerance is prerequisite to develop such molecular marker-assisted breeding. In this study, Bulked Segregant Analysis (BSA) was used to screen molecular markers associated with salt-alkali tolerance trait in P. trituberculatus. Two DNA mixing pools with significant difference in salt-alkali tolerance were prepared and 94.83G of high-quality sequencing data was obtained. 855 SNPs and 1051 Indels were firstly selected as candidate markers by BSA analysis, out of which, 20 markers were further selected via △index value (close to 0 or 1) and eight of those were successfully verified. In addition, based on the located information of the markers in genome, eight candidate genes related to salt-alkali tolerance were anchored including ubiquitin-conjugating enzyme, aspartate–tRNA ligase, vesicle-trafficking protein, and so on. qPCR results showed that the expression patterns of all these genes changed significantly after salt-alkali stress, suggesting that they play certain roles in salt-alkali adaptation. Our results will provide applicable markers for molecular marker-assisted breeding and help to clarify the mechanisms of salt-alkali adaptation of P. trituberculatus.